The Ultimate GUI Framework: Are We There Yet? - Stokke Knut Anders; Barash Mikhail; Järvi Jaakko (Germany, 2025)
The programming community seems to be forever searching for the ultimate user interface programming approach and the accompanying framework. We describe the landscape of recent efforts in this quest through describing commonalities and differences of modern JavaScript frameworks with respect to their approaches to GUI specifications. We situate both Eelco Visser’s work on WebDSL and our own work on GUI programming in this landscape, and point out areas where more research is needed, including modeling multi-way dataflows and dynamic structures in GUIs.
Eelco Visser Commemorative Symposium: EVCS 2023, April 5, 2023, Delft, The Netherlands